2014
DOI: 10.1080/00071668.2013.864381
|View full text |Cite
|
Sign up to set email alerts
|

The effect of feeding excess arginine on lipogenic gene expression and growth performance in broilers

Abstract: 1. Reducing excess fat accretion is important for both human health and animal production. The present study was conducted to investigate the effects of arginine (Arg) on the regulation of lipogenic gene expression and on growth performance. 2. One-d-old female broiler chicks (Ross, n = 192) were used in a completely randomised design with 4 dietary treatments in which diets included 100% (CTL), 153% (LArg), 168% (MArg) and 183% (HArg) of the recommended concentration of digestible Arg. 3. Results showed that … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

5
31
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 32 publications
(36 citation statements)
references
References 14 publications
5
31
0
Order By: Relevance
“…Tangara et al (2010) reported higher body weight of ducks at 0 and 7 days post-hatch with in ovo injection of 1.2 ml solution of 0.11% arginine. Moreover, feeding high levels of arginine during the rearing period increased daily weight gain and feed conversion ratio (Ebrahimi et al, 2014;Xu et al, 2018). Moreover, feeding high levels of arginine during the rearing period increased daily weight gain and feed conversion ratio (Ebrahimi et al, 2014;Xu et al, 2018).…”
Section: Discussionmentioning
confidence: 97%
See 3 more Smart Citations
“…Tangara et al (2010) reported higher body weight of ducks at 0 and 7 days post-hatch with in ovo injection of 1.2 ml solution of 0.11% arginine. Moreover, feeding high levels of arginine during the rearing period increased daily weight gain and feed conversion ratio (Ebrahimi et al, 2014;Xu et al, 2018). Moreover, feeding high levels of arginine during the rearing period increased daily weight gain and feed conversion ratio (Ebrahimi et al, 2014;Xu et al, 2018).…”
Section: Discussionmentioning
confidence: 97%
“…Meanwhile, in ovo injection of different ratios of l-arginine to l-lysine improved day-old chicks' weight (Ebrahimi et al, 2018). Moreover, feeding high levels of arginine during the rearing period increased daily weight gain and feed conversion ratio (Ebrahimi et al, 2014;Xu et al, 2018).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Addition of excess L-Arg in diet increased fatty acid synthase mRNA expression in muscle and reduced lipoprotein lipase and Acetyl CoA carboxylase mRNA expression in abdominal fats in pigs [48] (Tan et al, 2011). The inclusion of medium and high level of L-Arg downregulated lipogenic genes (acetyl-coenzyme A carboxylase, FAS, and malic enzyme) in liver and adipose tissue of broiler chickens [49]. This implies that down regulation of expression of FAS in hepatic tissue will decrease the accessibility of fatty acids for synthesis of triglycerides and storage in body.…”
Section: Arginine and Lipogenic Gene Expressionmentioning
confidence: 98%